STUDENTS’ INTEREST IN GENERAL ENGLISH CLASS AND THEIR REACTION TOWARDS TEACHING METHODS - Maya Lisa Aryanti (Indonesian EFL Journal, 2017)
This article discusses about a few points which make the students interested in learning General English, students’ reaction on teaching method used by the lecturers, and additional description used to explain certain materials. This study is important because teaching non English Department students is challenging. This study is included into a qualitative research. The used theories are teaching-learning theories. Hence, the theories of research methodology and a few linguistic theories are taken. General English remains Basic English course given either in the first semester or in the second one. Through this research, it appears that discussion method and lecture method are still needed. However, the students will be more delight if learning process is supported by visual media or if they often get challenges. Further, General English materials still continue being developed as new curriculum is released.Keywords: general english, teaching method, students’ reaction